(untitled) (Fiep Bulletin - online, 2015)
This research is about the printed media discourse strategies that, in order to create expectations of a Gold Medal by the Brazilian male volleyball team in the Olympic Games of Athens 2004, set this event in the Brazilian sport society. The content analysis of related reports written at Folha de São Paulo (FSP) newspaper were studied from May to September 2004. These strategies were divided in two time groups: the Pre-Olympics Period and the Olympic Period. The identified categories in this study show how FSP newspaper presented the Brazilian Team as the favorite for the Olympic Gold and how it created expectations on the readers and fans; besides showing aspects of making up national sports idols.